"Sourd-Muet": The Poetics of Non-Communication in Peter Manson's 'Sourdough Mutation'. Issue 1 (15th May 2019) - Thomas, Greg
Abstract : This article explores the formal characteristics of, and some possible motivations for, what I call 'non-communication' in Peter Manson's 2014 poem-sequence 'Sourdough Mutation'. Initially, I consider the distinctions between the compositional mode which defines this sequence and those which had characterised Manson's previous poetry and prose – this distinction resting on a unique attentiveness in 'Sourdough Mutation' to the visual and sonic surfaces of language – before enumerating some of the grammatical, visual, and phonetic effects which generate this emphasis. I consider some potential influences on this aspect of the work, turning first to concrete poetry and secondly – and at greater length – to the Symbolist poetry of Stéphane Mallarmé. The main critical contention of this article is that 'Sourdough Mutation' partly constitutes a formal homage to the grammatical and phonetic playfulness of Mallarmé's poetry, an homage which could not have been incorporated into the translations of that poetry which Manson was concurrently producing because of his primary focus as a translator on the work's semantic dimensions. Defining 'Sourdough Mutation' as 'neo-symbolist' on this basis, I consider some potential readings of the sequence's political significance. Like Julia Kristeva's reading of Mallarmé's poetry, the non-communicative register of 'Sourdough Mutation' might manifest a disturbance in the boundaries of the socially-mediated linguistic subject, with revolutionary implications. However, I acknowledge the tendency of this 'Kristevan' reading to lead to repetitive analysis of experimental poetry, and in conclusion offer an alternative, more contextually attentive "political" reading of 'Sourdough Mutation', presenting its processes of formal permutation as analogies for the systems of financial exchange which precipitated the 2007–08 economic crash.